Acute myeloid leukemia cells adhere to bone marrow and acquire chemoresistance by downregulating UNC5B expression - Teng, Teng; Ren, Liping; Xiao, Jilong; Shi, Zhiyu (Frontiers in Oncology, 2024)
Acute myeloid leukemia (AML) is a malignant tumor of the hematological system. Because of its characteristics of recurrence, refractory and chemoresistance, new therapeutic targets need to be identified. Adhesion and proliferation are characteristics of AML cells, and critical steps in inducing chemotherapy resistance. In this study, we reported that UNC5B inhibits AML cell bone marrow adhesion, inhibits AML cell proliferation and increases sensitivity to chemotherapy. Mechanistically, RNA sequencing (RNA-seq) and experimental results revealed that overexpression of UNC5B inhibits adhesion and proliferation signaling pathways and inhibits the expression of MPZL1, CLDN23, IGF2 and WNT7B. In conclusion, our findings suggest that UNC5B serves as a prognostic indicator and a potential therapeutic target for AML.